Impact of Plasma Electron Flux on Plasma Damage‐Free Sputtering of Ultrathin Tin‐Doped Indium Oxide Contact Layer on p‐GaN for InGaN/GaN Light‐Emitting Diodes. Issue 2 (19th December 2017) - Son, Kwang Jeong; Kim, Tae Kyoung; Cha, Yu‐Jung; Oh, Seung Kyu; You, Shin‐Jae; Ryou, Jae‐Hyun; Kwak, Joon Seop
Abstract: The origin of plasma‐induced damage on a p ‐type wide‐bandgap layer during the sputtering of tin‐doped indium oxide (ITO) contact layers by using radiofrequency‐superimposed direct current (DC) sputtering and its effects on the forward voltage and light output power (LOP) of light‐emitting diodes (LEDs) with sputtered ITO transparent conductive electrodes (TCE) is systematically studied. Changing the DC power voltage from negative to positive bias reduces the forward voltages and enhances the LOP of the LEDs. The positive DC power drastically decreases the electron flux in the plasma obtained by plasma diagnostics using a cutoff probe and a Langmuir probe, suggesting that the repulsion of plasma electrons from the p ‐GaN surface can reduce plasma‐induced damage to the p ‐GaN. Furthermore, electron‐beam irradiation on p ‐GaN prior to ITO deposition significantly increases the forward voltages, showing that the plasma electrons play an important role in plasma‐induced damage to the p ‐GaN. The plasma electrons can increase the effective barrier height at the ITO/deep‐level defect (DLD) band of p ‐GaN by compensating DLDs, resulting in the deterioration of the forward voltage and LOP. Finally, the plasma damage‐free sputtered‐ITO TCE enhances the LOP of the LEDs by 20% with a low forward voltage of 2.9 V at 20 mA compared to LEDs with conventional e‐beam‐evaporated ITO TCE. Abstract : The plasma electrons, and not the ions, play a key role in causing plasma‐induced damage to the p ‐GaN during the sputtering of tin‐doped indium oxide. The repulsion of plasma electrons from the p ‐GaN surface using radiofrequency (RF) superimposed direct current (DC) (RF+DC) sputtering with positive DC power greatly enhances the light output power of the light‐emitting diodes by 20% with a low forward voltage of 2.9 V at 20 mA.